Uncovering heterogeneity of local lattice distortion in TiZrHfNbTa refractory high entropy alloy by SR-XRD and EXAFS. (15th January 2023) - Tan, Yuan-Yuan; Li, Tong; Chen, Yu; Chen, Zhong-Jun; Su, Ming-Yao; Zhang, Jing; Gong, Yu; Wu, Tao; Wang, Hai-Ying; Dai, Lan-Hong
Abstract: Local lattice distortion is usually hypothesized to be severe in TiZrHfNbTa refractory high entropy alloy (RHEA). However, few works have made to quantitatively evaluate element specified distortion and its effect on mechanical behavior of this alloy. In this work, we herein provide a quantitative assessment of element specified local lattice distortion in both the as-prepared and tested TiZrHfNbTa RHEA using a combination of X-ray diffraction and extended X-ray absorption fine structure spectrum (EXAFS). The results show a more significant local lattice distortion (5.2 ± 0.3%) around Zr-center than that (4.0 ± 0.4%) around Nb-center in the as-prepared TiZrHfNbTa RHEA, and the distortion magnitude become more prominent after tensile test. Splitting features are observed in the Fourier transformed EXAFS spectra due to heterogeneous atom motions during deformation. The underlying mechanisms of this element-specified local distortion and its influence on solid solution hardening and ductility degradation are discussed as well. Graphical abstract: Image, graphical abstract We quantitatively assessed local lattice distortion of TiZrHfNbTa RHEA in the as-prepared and tested state by a combination of SR-XRD and EXAFS. The results show an increase of local lattice distortion and re-ordering of atoms from the as-prepared to the tested state.